Calcium and Signal Transduction - Buchholz, John N.; Behringer, Erik J. (Physiology, 2018)
Since the development of microelectronic clamping methodology and fluorescent indicators for direct measurement of dynamic intracellular calcium transients, our understanding of biological signal transduction has progressed dramatically since the 1980s. Calcium is a universal signal in biology that modulates gene expression, transmitter and hormone release, muscular movement, and even "programmed" cell death. This book represents a compilation of chapters from a diverse set of expert biologists throughout the world who have conducted research in the general area of calcium signaling in organisms ranging from bacteria to humans. In accord with priorities of resolving human disease, the reader will also benefit from learning calcium's role in cellular signaling pathology relating to acute or chronic conditions such as vomiting, sepsis, obesity, hypertension, and cancer.